Thermally assisted quantum annealing of a 16-qubit problem - Dickson N. G.; Johnson M. W.; Amin M. H.; Harris R.; Altomare F.; Berkley A. J.; Bunyk P.; Cai J.; Chapple E. M.; Chavez P.; Cioata F.; Cirip T.; et al. (2013, 2013)
Title screen